International Lawfare and Transactional Peacemaking: Indonesia’s ‘Board of Peace’ and the Question of Palestinian Sovereignty - Chairul Fahmi; Muhammad Siddiq Armia; Mizaj Iskandar; Laila Muhammad Rasyid; Faisal Fauzan (Faculty of Law Universitas Trunojoyo Madura, 2026)
The Board for Peace (BoP), established by President Trump, is integral to the execution of the America-First and transactional strategy. This board indicates a transition in international collaboration from multilateralism under the UN mandate to a multi-corporate framework for handling the post-conflict transition in Gaza. This article analyses the legitimacy of the BoP under international law and the ramifications of Indonesia's permanent membership and its allocation of one billion US dollars to the BoP, while also evaluating its implications for Palestinian sovereignty and the international legal system. This research utilizes an interdisciplinary approach that combines international law, political economy, and international relations. The research indicates that the creation of the BoP was prompted by UN Security Council Resolution 2803, although it has diverged from the resolution's aims. Moreover, the BoP has invalidated the 2024 Advisory Opinion of the International Court of Justice (ICJ) about the Palestinian people's right to self-determination. Moreover, the BoP, which possesses a comprehensive strategy for Gaza's reconstruction post-Israel's devastation, represents an infringement on the rights of the Palestinian populace in Gaza, undermines Palestinian sovereignty, overlooks the Palestinian Authority, and imposes a fiscal obligation on nations, especially permanent members like Indonesia. This paper asserts that the BoP framework is designed exclusively to sustain informal imperialism that advantages Israel, hinders the two-state solution, and constrains Indonesia’s foreign policy—ideally independent and proactive—under the influence of U.S. interests during the Trump administration.